Predictors and clinical significance of local recurrence in extremity soft tissue sarcoma. (May 2013) - Alamanda, Vignesh K.; Crosby, Samuel N.; Archer, Kristin R.; Song, Yanna; Schwartz, Herbert S.; Holt, Ginger E.
Abstract Background. Limb salvage surgery (LSS) has gained widespread acceptance as the current treatment for treating extremity soft tissue sarcoma (STS) and has been greatly refined since its inception. Combined with improved adjuvant treatment modalities, rates of local relapse have greatly decreased. Nonetheless, local recurrence still occurs and identifying the cause and the subsequent effects of local recurrence can provide valuable insights as LSS continues to evolve. Methods. This retrospective study evaluated 278 patients treated for STS of the extremities between 2000 and 2006. Of these, 41 patients developed a local recurrence while 247 did not. Tumor characteristics and prognostic outcomes were analyzed. Wilcoxon rank sum test and either χ2 or Fisher's exact was used to compare variables. Kaplan Meier and Gray's test for cumulative risk were also performed. Results. Patients who had a positive margin were 3.76 times more likely to develop local recurrence when compared to those with negative margins. This corresponds to a 38% risk of local recurrence if the margins were positive after six years vs. 12% if the margins were negative. In patients who underwent a re-excision, the presence or absence of residual disease upon re-excision did not have any bearing on local recurrence (p = 0.27). In comparing patients with and without local recurrence, there was no statistically significant difference in the rate and the proportion encountering distant metastasis and death due to sarcoma (p > 0.05). Conclusions. Despite advancements in surgery, radiation and imaging, positive margins still occur, and the presence of positive margins following definitive treatment continues to remain as a strong predictor for local recurrence. While local recurrence represents a negative outcome for a patient, its impact on future prognosis is influenced by a variety of factors such as time to local recurrence as well as the tumor's inherent biological characteristics.